(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the dynamics of the housing stock growth in the Republic of Uzbekistan, as well as issues related to their maintenance, repair, and management system. The main purpose of the current paperwork is to study the housing management system of the country and clarify the implementation of the best method of management for a high level of satisfaction of the population. Findings of the article can be discussed: the relationship of private housing funds in the case of satisfaction according to the survey is positive, and even new organized professional housing companies service quality does not match the minimum requirement. Practical suggestions and recommendations for improving the management system and increasing the efficiency of using the housing stock are also examined.